Efficacy and Safety of Stereotactic Radiotherapy in Patients With Recurrent Ventricular Tachycardias: The Czech Experience - Hašková, Jana; Wichterle, Dan; Kautzner, Josef; Šramko, Marek; Peichl, Petr; Knybel PEng, Lukáš; Jiravský, Otakar; Neuwirth, Radek; Cvek, Jakub (JACC. Clinical electrophysiology, 2024)
BACKGROUND: Stereotactic arrhythmia radiotherapy (STAR) has been proposed recently in patients with refractory ventricular tachycardia (VT). OBJECTIVES: The purpose of this study was to describe the efficacy and safety of STAR in the Czech Republic. METHODS: VT patients were recruited in 2 expert centers after at least 1 previously failed catheter ablation (CA). A precise strategy of target volume determination and CA was used in 17 patients treated from December 2018 until June 2022 (EFFICACY cohort). This group, together with an earlier series of 19 patients with less-defined treatment strategies, composed the SAFETY cohort (n = 36). A dose of 25 Gy was delivered. RESULTS: In the EFFICACY cohort, the burden of implantable cardioverter-defibrillator therapies decreased, and this drop reached significance for direct current shocks (1.9 ± 3.2 vs 0.1 ± 0.2 per month; P = 0.03). Eight patients (47%) underwent repeated CA for recurrences of VT during 13.7 ± 11.6 months. In the SAFETY cohort (32 procedures, follow-up >6 months), 8 patients (25%) presented with a progression of mitral valve regurgitation, and 3 (9%) required intervention (median follow-up of 33.5 months). Two cases of esophagitis (6%) were seen with 1 death caused by the esophago-pericardial fistula (3%). A total of 18 patients (50%) died during the median follow-up of 26.9 months. CONCLUSIONS: Although STAR may not be very effective in preventing VT recurrences after failed CA in an expert center, it can still modify the arrhythmogenic substrate, and when used with additional CA, reduce the number of implantable cardioverter-defibrillator shocks. Potentially serious sides effects require close follow-up.
Keywords: recidiva; complications; Humans; lidé středního věku; stereotactic arrhythmia radiotherapy (STAR); Female; Aged; výsledek terapie; senioři; lidé; katetrizační ablace; catheter ablation; ventricular tachycardia; radiochirurgie; Radiosurgery; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Czech Republic; defibrilátory implantabilní; Recurrence; komorová tachykardie; Česká republika; mužské pohlaví; Catheter Ablation; Defibrillators, Implantable; Tachycardia, Ventricular